2022
DOI: 10.1186/s41065-022-00256-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cynarine for treatment of non-alcoholic fatty liver disease based on the integration of network pharmacology, molecular docking and cell experiment

Abstract: Background Nonalcoholic Fatty Liver Disease (NAFLD) is a chronic Liver Disease prevalent all over the world. It has become more and more common in Japan, China and most western developed countries. The global prevalence rate is 25.24%, and the trend is increasing year by year. Related studies have shown that Cynarine has certain liver protection, lipid lowering and immune intervention effects. So, this study to systematically predict and analyze the mechanism of Cynarine in the treatment of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Cynarine is a caffeoylquinic acid molecule isolated from the Traditional Chinese Medicine artichoke ( Cynara scolymus L.) that possesses anti-obesity and antioxidant liver properties in high-fat diet-induced obese mice [ 44 ]. With a binding energy of -14.68 kcal/mol in this investigation, cynarin had the highest binding affinity of all the mentioned cinnamic acid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Cynarine is a caffeoylquinic acid molecule isolated from the Traditional Chinese Medicine artichoke ( Cynara scolymus L.) that possesses anti-obesity and antioxidant liver properties in high-fat diet-induced obese mice [ 44 ]. With a binding energy of -14.68 kcal/mol in this investigation, cynarin had the highest binding affinity of all the mentioned cinnamic acid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the key components of artichoke, Cynarine has been valued by many scholars. Sun and their research team ( Sun, et al, 2022a ) found that there were 48 intersection targets of Cynarine and NAFLD, among which TP53, ELANE, MMP9, CASP3, and NOTCH1 were the core therapeutic targets. Through the PPI network, inflammation and immune-related targets played a key therapeutic role.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%